THE DEVELOPMENT OF COMPONENTS AND INDICATORS OF SURVIVAL SKILLS WHEN ENCOUNTERING DANGERS FOR EARLY CHILHOOD STUDENTS - Khongcharoen, Pratheep; Prasit, Juthamas (Journal of Education and Innovation, 2025)
This study aimed to develop components and indicators of survival skills when encountering dangers for early childhood students. It also aimed to investigate the construct validity of components and indicators of survival skills when encountering dangers for early childhood students. The participants included 354 early childhood teachers from schools and child development centers in Thailand. Structured interviews, suitability evaluation forms, and questionnaires constituted research instruments. Content analysis, descriptive statistics, and a second order confirmatory factor analysis were used for data analysis. The finding revealed that: (1) The components and indicators of survival skills for early childhood students when encountering dangers included 4 factors that were the component of control (3 indicators), the component of origin and ownership (3 indicators), the component of reach (3 indicators), and the component of endurance (2 indicators). (2) A second order confirmatory factor analysis of survival skills for early childhood students when encountering dangers showed that the model was consistent with the empirical data from the Chi-squared test ( (df = 35, n = 354) = 42.492, p = .101, CFI = .997, TLI = .993, RMSEA = .024, SRMR = .011). The factor loadings of 4 components and 11 indicators were 0.814 – 0.993 and 0.637 – 0.816 respectively. The model also had construct validity, with factor loadings showing statistical significance at the .01 level on all indicators.